Should we base training prescription on the force-velocity profile? Exploratory study of its between-day reliability and differences between methods - Valenzuela, P. L.; Martínez, G. S.; Torrontegi, E.; Carrión, J. V.; Montalvo, Z.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To analyze the differences in the force-velocity (F-v) profile assessed under unconstrained (ie, using free weights) and constrained (ie, on a Smith machine) vertical jumps, as well as to determine the between-day reliability.